Peran Inkubator Bisnis dalam Membangun Startup pada Perguruan Tinggi - Lutfiani, Ninda; Rahardja, Untung; Manik, Ita Sari Perbina (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
Startups are sufficiently developed in Indonesia to become a trend in business incubators that include college or university students. This is due to the incubation concept and program offered to prospective entrepreneurs who have potential ideas in business. Thus, research was conducted to determine the role of business incubators in building startups in universities. But there are obstacles in developing startups, limited technology, leadership and management. The study was conducted at the Alphabet Incubator of Raharja University with a qualitative approach. The research method used is the method of observation and literature review by collecting data that aims to simplify the process. It can be seen how the government encourages business incubators in developing startups and introducing business through technology. The research objective is to increase innovation or creativity in developing successful new startups in higher education. Seen from students utilizing the facilities at the Alphabet Incubator to develop small businesses in the digital industry to increase workforce.Keywords: Business Incubator; Startup; Innovation or CreativityStartup cukup berkembang di Indonesia sehingga menjadi trend dalam inkubator bisnis yang mencakup mahasiswa atau mahasiswi di perguruan tinggi. Hal ini disebabkan konsep dan program inkubasi yang ditawarkan kepada calon wirausaha yang mempunyai ide potensial dalam bisnis. Sehingga penelitian dilakukan untuk mengetahui peran inkubator bisnis dalam membangun startup pada perguruan tinggi. Namun terdapat kendala dalam mengembangkan startup, terbatasnya teknologi, kepemimpinan dan manajemen. Penelitian dilakukan di Alphabet Incubator Universitas Raharja dengan pendekatan kualitatif. Metode penelitian yang digunakan adalah metode observasi dan literature review dengan mengumpulkan data yang bertujuan untuk mempermudah proses pengerjaannya. Dapat dilihat bagaimana pemerintah mendorong inkubator bisnis dalam mengembangkan startup dan mengenalkan bisnis melalui teknologi. Tujuan penelitian untuk meningkatkan inovasi atau kreativitas dalam mengembangkan startup baru yang sukses di perguruan tinggi. Terlihat dari mahasiswa memanfaatkan fasilitas di Alphabet Incubator untuk mengembangkan usaha kecil dalam industri digital untuk peningkatan tenaga kerja.Kata Kunci: Inkubator Bisnis; Startup; Inovasi atau Kreativitas